Institutional roots inertia and participatory governance in Brazil - Brumatti, Lívia Martinez (2022)
Citizen participation in public decision-making processes has been presented difficulties in being established and has suffered setbacks and advances. This thesis analyzes the roots of long-standing institutional logics and how \"non-participatory\" elements of these logics induce or facilitate such setbacks. I adopted an interpretive perspective and analyzed two types of participatory governance arrangements: Citizen Advisory Municipal Councils in the health area and the area of child and adolescent rights in medium-sized municipalities in the state of Rio Grande do Sul; and the case of Participatory Budgeting (PB) in Porto Alegre. Municipal Councils are established by a federal law that obliges municipalities to implement these initiatives for validating public policies. On the other hand, Participatory Budgeting is a voluntary initiative that does not have any imposition from other government bodies. I have conducted interviews with several actors involved in decision-making processes in my fieldwork. The analysis showed that the elite-patrimonial, the legalistic-bureaucratic, and the managerial logics present in Brazilian public administration have an inertial force (related to their long-standing existence) that interpenetrates the practices and dynamics of these arrangements and hybridizes with the citizen-participatory logic. In the case of Municipal Councils, the hybridization of logics makes, for the most part, councils dependent on actors with power and reflexivity (called institutional entrepreneurs) who support initiatives throughout the different terms facing the challenges to preserve the space for citizen participation. Otherwise, the councils are at the mercy of patrimonial practices that legitimize the arrangement in a distorted way. At the same time, the very existence of Participatory Budgeting only seems to be possible with the emergence of an institutional entrepreneur who puts a lot of effort and agency (given the great strength of conflicting long-standing institutional logics) in implementing the citizen-participatory logic in local contexts. Even if there is this entrepreneur, there are no guarantees actors will carry out the practices within these arrangements in a purely altruistic manner and effectively meet public demands.